Pola Pendidikan Islam dalam Pendidikan Anak - M.Pd.I., Masita (LP2M Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: Patterns of Islamic education in children's education, it is fitting for Muslims to pay attention to children's education and individual development to achieve the title